2020
DOI: 10.1186/s12884-020-03228-9
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression in mothers and fathers: a structural equation model

Abstract: Background Post-partum depression (PPD) is a growing mental health concern worldwide. There is little evidence in the Chinese context of the relationship between paternal PPD and maternal PPD. Given the growing global concerns this relationship requires further exploration. Methods A survey was conducted with 950 total couples from March 2017 to December 2018. The study was conducted using a standardized questionnaire that included basic demographic information, information on the relationship between the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…Both direct and indirect effects are expressed as the standardized regression coe cient (β) and 95%CI, and bivariate analysis was employed to assess the associations between all variables (13). Relative chi-square (χ 2 /df), goodness-of-t index (GFI), comparative t index (CFI), Tucker-Lewis t index (TLI) and the root mean-square error of approximation (RMSEA) were used to assess model t (31).…”
Section: Discussionmentioning
confidence: 99%
“…Both direct and indirect effects are expressed as the standardized regression coe cient (β) and 95%CI, and bivariate analysis was employed to assess the associations between all variables (13). Relative chi-square (χ 2 /df), goodness-of-t index (GFI), comparative t index (CFI), Tucker-Lewis t index (TLI) and the root mean-square error of approximation (RMSEA) were used to assess model t (31).…”
Section: Discussionmentioning
confidence: 99%
“…Although perceived support and marital satisfaction have been seen as strong predictors of maternal depressive symptoms [2,10], few studies examined the effect of marital satisfaction and perceived support on fathers' depressed mood while controlling the effect of financial stress. Previous studies suggested that paternal depression and maternal depression are correlated, and the correlation can partially be explained by marital quality [35,36]. More dyadic studies of paternal and maternal depressed moods are needed to understand if marital satisfaction is only related to paternal depressed mood when maternal depression is present in the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies investigating factors associated with PPD involving both parents are needed to construct effective preventive strategies. Previous longitudinal studies that included both parents have shown that mother‐in‐law and daughter‐in‐law relationship satisfaction, mutual depression, and marital relationship satisfaction are related to PPD 27,28 . A previous study of married couples in Japan reported that history of mental health disorders, household income, infant disease under medical treatment, partner depression, and marital satisfaction were associated with PPD in fathers 17,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous longitudinal studies that included both parents have shown that mother-in-law and daughter-in-law relationship satisfaction, mutual depression, and marital relationship satisfaction are related to PPD. 27,28 A previous study of married couples in Japan reported that history of mental health disorders, household income, infant disease under medical treatment, partner depression, and marital satisfaction were associated with PPD in fathers. 17,29 However, their study conducted in Japan investigated only one (after 4 months) or two (after 1 month and 6 months) time periods between 1 and 6 months postpartum.…”
mentioning
confidence: 99%